The Role of Women’s Political Leadership (Case Study: Senggreng Village, Malang Regency) (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
Addressing the interests and needs of women is a fundamental aspect of the development process, especially within village contexts. This is not only important for producing policies that meet women’s needs but also for accommodating the interests of other marginalized groups that have historically been overlooked. Currently, village head positions in Malang Regency remain predominantly held by men. Indirectly, this indicates that the resulting development policies have not yet adequately addressed the needs of women in villages across Malang Regency. However, Senggreng Village, under the leadership of a female village head, has successfully accommodated the needs of women, particularly in the areas of Village Development and Community Empowerment. The findings of this study revealed that the Village Head of Senggreng implements innovative, responsive, and participatory approaches in formulating developmental policies and programs